Online coupling of digital microfluidic devices with mass spectrometry detection using an eductor with electrospray ionization - Baker, Christopher A. (2012)
MS detection coupled with digital microfluidic (DMF) devices has only been demonstrated in an off-line manner using matrix assisted laser desorption ionization. In this work, an eductor is demonstrated which facilitated online coupling of DMF with electrospray ionization MS detection. The eductor consisted of a transfer capillary, a standard ESI needle, and a tapered gas nozzle. As a pulse of N(2) was applied to the nozzle, a pressure differential was induced at the outlet of the ESI needle that pulled droplets from the DMF, past the ESI needle, and into the flow of gas exiting the nozzle, allowing detection by MS. Operating position, ionization potential, and N(2) pressure were optimized, with the optimum ionization potential and N(2) pressure found to be 3206 V and 80 psi, respectively. Online MS detection was demonstrated from both open and closed DMF devices using 2.5 μL and 630 nL aqueous droplets, respectively. Relative quantitation by DMF-MS was demonstrated by mixing droplets of caffeine with droplets of theophylline on an open DMF device, and comparing the peak area ratio obtained to an on-chip generated calibration curve. This eductor-based method for transferring droplets has the potential for rapid, versatile, and high throughput microfluidic analyses.